Crushmore : essays on love, loss, and coming-of-age - Badgley, Penn, 1986-; Kavelin, Nava, 1984-; Ansari, Sophie (Gallery Books, 2025)
"In the debut essay collection from the hosts of the hit podcast Podcrushed, Penn Badgley, Sophie Ansari, and Nava Kavelin explore what it means to come of age at every stage of our lives. Known for spotlighting your favorite artists' tween stories of self-discovery ontheir podcast, Penn, Sophie, and Nava turn inward to share their own experiences for the first time. Penn, a twelve-year-old, Discman-toting introvert, starts in the solitude of his only-child household where he danced like no one was watching (because no one was watching) before embarking on a neon-lit journey to Hollywood. Sophie takesus to her middle school in Beijing where she had to ward off rumorsof a boob job, and to the moment loosening her chokehold on love brought her husband straight into her living room. Nava traces the emotional aftershocks of losing her mother and guides us through the whimsical world of an imaginationship, where nothing is ever as it seems. With compassion, humor, and insight, Crushmore charts the often cringey, sometimes luminous path from adolescence to adulthood. Together, these essays remind us that we can find healing--and even inspiration--from our awkward adolescent selves long after we thought weleft them behind"--